The experience and influence of social support and social dynamics on cardiovascular disease prevention in migrant Pakistani communities: A qualitative synthesis. Issue 4 (April 2018) - Kokab, Farina; Greenfield, Sheila; Lindenmeyer, Antje; Sidhu, Manbinder; Tait, Lynda; Gill, Paramjit
Highlights: Stereotyping by professionals and community members can limit preventative health behaviours. Interpersonal factors e.g. family support limits women's ability to access preventative care. Professionals and health services should recognise social context influences lifestyle changes. Abstract: Objective: The objective of this research was to synthesise qualitative literature about the perceived influence and experience of social support, in relation to cardiovascular disease (CVD) prevention in migrant Pakistani communities. Methods: Articles were systematically reviewed, critically appraised, and analysed using an adapted meta-ethnography approach. Results: Sixteen qualitative studies on health behaviours related to CVD prevention were included. Findings: include four sub-themes under two substantive thematic areas that focus on: 1) family dynamics and 2) community dynamics influenced by discrimination. For members of the Pakistani community, gendered family dynamics and discrimination from outside and within community networks influenced behaviour change. Conclusion: The authors of the synthesis developed multi-layered, contextualised interpretations of the care needs of an established multi-generational community. Future qualitative studies taking an intersectional approach to interpreting the role of social networks in migrant communities should take into account gender, identity, culture and faith. Practice implications: Health care providers should focus on cultural awareness and sensitivity during consultations. In particular, general practitioners can benefit from the insight they gain from patient experiences, allowing for more appropriate recommendations.